The Indonesian Syntactic Structure Interfere into English Sentences: An Interlanguage Study - Bahar Bahar; Dahlia Husain; Eko Aprianto (BIRCU, 2019)
The reason for conducting this research was based on consideration that university students majoring in English should be at the level where their English is considered good. Unfortunately, students still made errors in both spoken and written form. In this study, 20 students of English Department at Fajar University enrolled which were taken by total samplingmethod. This research is aimed to provide useful information particularly as referencefor English teachers, lecturers and curriculum developers about the extent of theIndonesian syntactic structure that interfere the students in making English sentence.A mix method was applied in which the data was analysed both qualitatively andquantitatively. The conclusion of the result shows that the students still have problemsin making English sentences. They still make errors in forming English sentences thatbased on the Indonesian form. Further, the most errors are found are the error of omissions. It is proven by the findings that the interference of Indonesian syntactic formis the main cause of student’s error in making English sentence.